The scope of periodontal practice of general dental practitoners in Manila - Bati, Anne Therese D.; Cabrera, Joyce Anne P. (Manila Department of Community Dentistry, University of the Philippines Manila, 2016)
Introduction: According to the Fourth National Monitoring and Epidemiological Survey (1998), around 78% of Filipinos are affected by periodontal disease. Given this and the limited number of periodontal specialists in the country, general dentistry practitioners are expected to at least provide disease control to the populace. This study determined the current state of periodontal practice by general dental practitioners of the Manila Dental Chapter.
Methods: A simple descriptive quantitative reseach design and convenience sampling was utilized in the study. A 20-item survey questionnaire was distributed attendees of the 74th annual convention and scientific session hosted by the Manila Dental Chapter, the kick off program of the oral health month by the members of the Manila Health Society and to private clinics located around Manila. The data was encoded and analyzed using the Statistical Package for the Social Sciences (SPSS) version 17.
Results: Among 140 dentists, statistical analysis of the data showed that 14% of the respondents probe first tima patients. Approximately 70% of dentists use a periodontal probe in checking bleeding on probing and furcation involvement. In using the periodontal probe, on;y 60% would insert until the base of the pocket. Furthermore, 33% of general practitioners employ the new classification of periodontal diseases. In terms of treatment, 89.3% perform scaling and polishing on gingivitis patients, while only 40% would do non-surgical root planing on periodontitis patients. Eighty-seven percent (87%) of respondents would formulate recall programs after treatment. Meanwhile, 116 dentists would refer periodontal cases for various reasons.
Conclusion: The results suggest that the periodontal practice of majority of general dental practitioners in Manila is confined to ocular examination, optional periodontal probing and scaling and polishing.
Seminar Paper (Doctor of Dental Medicine)--University of the Philippines Manila.
Keywords: Dentistry--Practice.; Periodontal diseases